Composting and vermicomposting of spent mushroom substrate for organic fertiliser and cultivation of Schizophyllum commune / Nolisa Madrim - Nolisa , Madrim (2018)
An increase in spent mushroom substrate (SMS) disposal as a result of continuous mushroom cultivation will give negative impacts towards the environment. The problem has attracted the attention of many researchers to explore the potential of SMS that still contains high beneficial nutrients after mushrooms cultivation. Reutilizing SMS not only help to reduce the environmental problems but will also benefit farmers economically. Schizophyllum commune is popularly consumed in Malaysia due to its delicious taste and medicinal benefits. The cultivation of S. commune has increased due to the increase in demand and the short turnover in its cultivation of one month. As a result, large amounts of SMS needs to be disposed. Hence, in this study, the potential of recycling spent S. commune substrate via composting and vermicomposting was investigated. SMS of S. commune was mixed with goat manure (GM) using three different formulations, 80 SMS:20 GM, 60 SMS:40 GM and 50 SMS:50 GM. The mixtures undertake composting and vermicomposting for 90 days. Samples for analysis of carbon:nitrogen (C/N) ratio and nutrient content (NPK) was taken on day 30, day 60 and day 90 of composting/vermicomposting. The compost and vermicompost were then tested as a fruiting substrate for S. commune cultivation by using different substrate formulations. This study revealed that the compost and vermicompost produced after 90 days of decomposition has a low C/N ratio. Among all the compost and vermicompost, compost formulation C (50 SMS:50 GM), compost formulation B (60 SMS:40 GM) and vermicompost formulation C (50 SMS:50 GM) are suitable to be used as organic fertiliser with C/N ratios of CC (23:34), CB (22.66) and VC (21.7). They also have high nitrogen, phosphorus and potassium (NPK) content, CC (N=1.61%, P=0.73%, K=0.81%), CB (N=1.54%, P=0.74%, K=0.63%) and VC (N=1.51%, P=0.81%, K=0.97%). Whereas, for S. commune cultivation, compost CC supplemented with 80% sawdust and 10% rice bran resulted in potentially high mushroom yield of, 80.25 g/bag with biological efficiency, 20.06%. The study also revealed that SMS of S. commune had C/N ratio, 66.92 which is almost similar to the C/N ratio of S. commune standard formulation, 61.69. Last but not least, the mushroom bags using compost and vermicompost in S. commune substrate formulation have no contamination throughout the cultivation period.